2013
DOI: 10.1111/resp.12061
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bronchial hyperresponsiveness and lung function in children age 5 and 6 with and without asthma

Abstract: Our data suggest that it not possible to distinguish preschool children with asthma from non-asthmatic wheezers based on their bronchial sensitivity and that the baseline Rrs has a strong effect on the bronchial reactivity in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Bronchial hyper-responsiveness studies comparing FOT with different lung function measures have reported FOT to be as effective as spirometry[ 63 - 69 ] and as sensitive as body plethysmography[ 70 ] and transcutaneous PO 2 [ 50 ] in older children with asthma. BHR has been assessed using FOT in children younger than 7 years of age with a range of challenge tests including adenosine monophosphate (AMP)[ 19 ], cold air[ 24 ], normal saline[ 21 ] methacholine[ 22 , 62 , 63 , 66 , 68 , 71 ], mannitol[ 25 ] and exercise[ 20 , 72 ] demonstrating that FOT can be reliably used in young children for challenge testing.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchial hyper-responsiveness studies comparing FOT with different lung function measures have reported FOT to be as effective as spirometry[ 63 - 69 ] and as sensitive as body plethysmography[ 70 ] and transcutaneous PO 2 [ 50 ] in older children with asthma. BHR has been assessed using FOT in children younger than 7 years of age with a range of challenge tests including adenosine monophosphate (AMP)[ 19 ], cold air[ 24 ], normal saline[ 21 ] methacholine[ 22 , 62 , 63 , 66 , 68 , 71 ], mannitol[ 25 ] and exercise[ 20 , 72 ] demonstrating that FOT can be reliably used in young children for challenge testing.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline lung function by spirometry [26] and the IOS [27] are the major determinants for measuring BHR. It is well known that the IOS parameters, particularly Rrs, are more sensitive to changes in airway obstruction than other lung function tests [10, 14, 15, 28].…”
Section: Discussionmentioning
confidence: 99%
“…challenges were performed by Astograph aerosol generator (J-21; Chest Company; Tokyo, Japan) delivered increasing doses of methacholine from 12 serially arranged nebulizers (17). Dmin was the cumulative dose of methacholine at the inflection point of the respiratory resistance (Rrs) tracing.…”
Section: Methacholine Inhalation Challenge Methacholine Inhalationmentioning
confidence: 99%